“Truth Vs. Slack Inducing” Paradox: How Does Compensation Scheme Mitigate Social Pressure on Budgetary Slack? - Aryan Danil Mirza. BR; Maria Paramastri Hayuning Adi (The Indonesian Journal of Accounting Research, 2020)
This research aims to examine the role of the compensation scheme in mitigating the negative impact of social pressure on the creation of budgetary slack. There are not clear phenomenon, how can compensation methods with pressure (penalty) actually be better able to reduce budgetary slack compared to compensation methods without penalty? This research contributes by validating the role of truth inducing and slack inducing compensation scheme in order to mitigate the budgetary slack through the perspective of expectancy theory. Results from experimental study among 56 undergraduate accounting students showed that obedience pressure tends to encourage individuals to create budgetary slack compared to while they experience pressure from the peers (H1). Another finding from this research is the tendency of individuals to create budgetary slack tends to be lower when they accept the slack inducing compensation mechanism than truth inducing (H2). These indicate that slack inducing compensation scheme is better used than truth inducing in mitigating the creation of budgetary slack. Different level of risk faced by the individual, especially in the absence of fines or sanctions if the budget target is not reached, give different impact on individual. Our research provides practical implication when individuals get stressed, compensation schemes are less effective in minimizing the effect of social pressure on the creation of budgetary slack.